Dietary chestnut bee pollen as an immunostimulant for rainbow trout (Oncorhynchus mykiss): Effects on the growth, haematological values, immune response, oxidant/antioxidant status, and survival against Aeromonas salmonicida subsp. achromogenes: Pollen as an immunostimulant in rainbow trout - İspir, Ünal and Mişe Yonar, Serpil and Yonar, M. Enis and Silici, Sibel (Cellular and Molecular Biology, 2023)
The present study was designed to assess the influence of dietary supplementation with chestnut bee pollen at various levels in rainbow trout, Oncorhynchus mykiss. For two weeks feeding period, a total of 300 fish were allocated into 12 fiberglass tanks and divided into four equal groups, three replicates each, with chestnut bee pollen (BP) dietary inclusion as follows; the fish group was given a basal diet (C); fish group fed a diet supplemented with BP 1% (BP-1); fish group fed a diet supplemented with BP 2% (BP-2); and fish group fed a diet supplemented with BP 4% (BP-3). At the end of the experiment, growth, haematological values, immune status, antioxidant status, and survival rate against Aeromonas salmonicida subsp. achromogenes were evaluated. Dietary supplementation with chestnut bee pollen significantly improves growth performance. Fish fed the diets containing chestnut bee pollen had higher the haematological values than those fed the control diet. The results showed that all the immunological parameters in the groups fed with chestnut bee pollen were significantly higher when compared to the control group. Moreover, dietary chestnut bee pollen increased disease resistance against Aeromonas salmonicida subsp. achromogenes compared to the control group. The tissue SOD, CAT and GSH-Px activities of groups fed with chestnut bee pollen significantly enhanced when compared with the control groups. In contrast, the tissue MDA levels in all groups fed with chestnut bee pollen were significantly decreased. The best values for the antioxidant parameters were determined in the groups fed with 2 and 4% of chestnut bee pollen. Overall, these findings suggest that dietary chestnut bee pollen enhances the growth, the haematological values, the immune and antioxidant response and increases disease resistance against rainbow trout.